Evaluation of Adjuvant Biomarkers in Acute Myocardial Infarction - M. V, Varghese; S. B, Gaikwad; M. M., Fawade; M. A., Bhattacharya (International Journal of Innovative Research in Medical Science, 2018)
Background: Acute myocardial infarction (AMI) is one of the dreadful complications of cardiovascular disease causing increasing mortality worldwide. The alterations (increase or decrease) of intracellular and extracellular enzymes or components in developing phase of disease are called markers. Variations in biochemical markers like Cardiac Troponins - T (ctnl) creatine kinase may correlate with the extent of myocardial damage in Acute myocardial infarction (AMI). Aim and Objectives: This study was undertaken to evaluate serum sodium, potassium, urea and creatinine as adjunctive parameters along with cardiac markers, which probably help in better prognosis of AMI. Material Methods: 100 subjects were included in this study with confirmed diagnosis of recent AMI by the physicians and 100 healthy persons visiting hospital for routine checkup. Blood samples of both group were analyzed for serum urea by Diacetylmonoxime, creatinine by Jaffe's, &sodium & potassium by flamephotometry uing Bio- Lab Diagnostic Kit Methods. Whereas cardiac troponin - T was done by chemiluminescence immunoassay (CLIA) on Lumax hormone analyser and CKMB by kinetic kit method. Results: There were statistically significant decreased levels of serum sodium (P<0.0001) potassium (p<0.0001), and elevated levels of urea (p<0.0001) and creatinine (0.0001) observed in AMI. Both established cardiac markers Trop- T and CKMB were extremely statistically significantly increased (p<0.0001) as compared to control group. Conclusion: This study showed association of routine blood tests such as urea, creatinine, sodiumand potassium hence can be used as supplement information with regard to treatment and better prognosis of AMI patients or these could be cost effective time saving adjuvant markers in management of myocardial infarction.